D(–)-Lactic Acid Producing Probiotics, D(–)-Lactic Acidosis and Infants. (1st November 2004) - Mack, David R
Abstract : There is mounting evidence that ingestion of selected probiotics can modify disease morbidity for specific conditions affecting humans, and there is growing interest in the amelioration or prevention of disease with probiotics. Modulation in gene expression of the cellular elements of the intestinal mucosa and interbacterial interactions are leading theories as to the mechanism whereby probiotics can effect benefit for the host. Furthermore, gene-environmental interactions are considered to be important in the development of disease in those at genetic risk. With the intestinal tract harbouring large numbers of bacteria, alteration of the microbial environment with probiotic microbes is being considered as a controllable factor that may limit disease expression for those at genetic risk. This reasoning has led to interest in the administration of probiotics to infants. However, there are significant developmental changes occurring in many organ systems from the time of parturition and during the first months of life. Because there is little in the published scientific medical literature regarding the effects of long-term administration of probiotics to infants, potential problems must be considered; one such issue is that of administration of D(-)-lactate-producing probiotics. An appraisal of the current knowledge of this potential adverse effect is the subject of this communication.